2015
DOI: 10.1088/0004-637x/807/1/79
|View full text |Cite
|
Sign up to set email alerts
|

RAPID VARIABILITY OF BLAZAR 3C 279 DURING FLARING STATES IN 2013−2014 WITH JOINTFERMI-LAT,NuSTAR,SWIFT, AND GROUND-BASED MULTI-WAVELENGTH OBSERVATIONS

Abstract: We report the results of a multi-band observing campaign on the famous blazar 3C 279 conducted during a phase of increased activity from 2013 December to 2014 April, including first observations of it with NuSTAR. The γ-ray emission of the source measured by Fermi-LAT showed multiple distinct flares reaching the highest flux level measured in this object since the beginning of the Fermi mission, with F(E > 100 MeV) of 10 −5 photons cm −2 s −1 , and with a flux doubling time scale as short as 2 hours. The γ-ray… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
143
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(154 citation statements)
references
References 83 publications
10
143
1
Order By: Relevance
“…For 3C279, the lower limit on the jet luminosity is which is close to the Eddington limit. A similar estimate was obtained by Hayashida et al (2015).…”
Section: C4543 and 3c279supporting
confidence: 87%
See 2 more Smart Citations
“…For 3C279, the lower limit on the jet luminosity is which is close to the Eddington limit. A similar estimate was obtained by Hayashida et al (2015).…”
Section: C4543 and 3c279supporting
confidence: 87%
“…The minumum detected variability time and gamma-ray luminosity were 4.5hr and 2 10 50 ergs −1 , respectively. Several similarly bright flares were detected form 3C279 in the period from 2013 December to 2014 April (Hayashida et al 2015). The GeV gamma-ray luminosity reached a level of and´-2 10 erg s 44 1 for 3C454.3 and 3C279, respectively.…”
Section: C4543 and 3c279mentioning
confidence: 85%
See 1 more Smart Citation
“…Rapid variability is also notably detected in many active galactic nuclei (AGNs). For example, the flat spectrum radio quasars (FSRQ) 3C 273 (e.g., Rani et al 2013) and 3C 279 (Hayashida et al 2015) produce GeV flares on hourly timescales; the radio galaxy IC310 (Aleksić et al 2014), the FSRQ PKS 1222+21 (Aleksić et al 2011), and several BL Lac objects, e.g., PKS 2155-304 (e.g., Aharonian et al 2007) and Markarian 501 (Albert et al 2007), are observed to flare in theTeV band with variability timescales of approximatelya few minutes. More strikingly, quite a few flares from blazars are found to be accompanied by large polarization angle swings in the optical band (Marscher et al 2008;Abdo et al 2010;Blinov et al 2015;Kiehlmann et al 2016), suggesting that the dissipation region has a coherent, strong magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling by Hayashida et al (2015) with a broken power-law EED showed that a very hard electron spectrum with p ∼ 1 below γ ′ b ∼ 3000 is required to explain this very hard Fermi -LAT spectrum. In the slowcooling regime, such a hard emitting electron spectrum requires a very hard injection electron distribution.…”
Section: Introductionmentioning
confidence: 99%